Stable formally zerovalent and diamagnetic monovalent niobium and tantalum complexes based on diazadiene ligands. - Daff, P; Etienne, M; Donnadieu, B; Knottenbelt, S; McGrady, J (2002)
This paper describes the efficient synthesis and full characterization of rare formally zerovalent and diamagnetic monovalent pseudooctahedral niobium and tantalum complexes. The reaction of NbCl(4)(thf)(2) with 4 equiv of Na and 3.5 equiv of iPr(2)-dad (1,4-diisopropyl-1,4-diaza-1,3-diene) yields Nb(iPr(2)-dad)(3) in 52% yield. Ta(iPr(2)-dad)(3) is also obtained in 33% yield from 5 equiv of Na/naphthalene and 3.5 equiv of iPr(2)-dad. Oxidation of these complexes with AgBPh(4) yields the diamagnetic complexes [M(iPr(2)-dad)(3)][BPh(4)] (M = Nb, Ta). X-ray and spectroscopic data indicate that the unpaired electron density is localized on the ligands. DFT calculations reveal that, in the prevailing D(3) symmetry, a very strong splitting of t(2g) metal-based orbitals occurs, leading to the diamagnetism of the 16e M(iPr(2)-dad)(3)(+). This strong splitting allows a M-N nonbonding, ligand-based orbital to accommodate additional electrons, as a result of which the formally zerovalent complexes, M(iPr(2)-dad)(3), are in fact correctly formulated as M(+)iPr(2)-dad (-), that is, (16e + 1e).